Hepáticas (Marchantiophyta) da Estação Científica Ferreira Penna, Floresta Nacional de Caxiuanã, Pará - (:unkn) unknown (Museu Paraense Emílio Goeldi, 2004)
During four years the inventory of the liverwort flora occurring in the Scientific Station Ferreira Penna was carried out, with the main objective of testing the hypothesis that a great floristic diversity of bryophytes would be found, as already determined for the arboreal flora. The methodology consisted in the analysis of bryophyte samples collected from the Station's various ecosystems: dense and open terra firme forests, várzea forests, igapó, campina and capoeira. For the identification, specialized bibliography was used, observing small portions of the rehydrated dried material. All identified material is being incorporated into the herbarium "João Murça Pires" of the Museu Paraense Emilio Goeldi (MG). A total of 637 samples were observed, identifying 2,264 specimens distributed in 78 species and one variety, 40 genera and 7 families of liverworts. The family Lejeuneaceae stood out for its high specific diversity and number of occurrences in the area. The species Ceratolejeunea comuta (Lindenb.) Schiffn. is the most abundant, with 261 occurrences. Three species have great ecological range because they were collected in all substrates and ecosystems studied. The corticolous substrate was preferred by 83% of the species. The highest specific diversity occurred in the floodplain ecosystem, but the dense terra firme forest presented the highest number of specimens. The new occurrence, for the state of Pará, of the species Lejeunea quinqueumbonata Spruce and the genus Yitaliantbus R.M.Schust. & Giancotti, with the identification of V. urubuensis Zartman & Ackerman and V. biscblerianus (Pôrto & Grolle) R.M.Schust. & Giancottti, and the inclusion of another 19 species not previously listed for the brioflora of the ECFPn confirm the great floristic diversity of bryophytes in the area, and as there is a large amount of unstudied collected material and many areas within the Station to be collected, these numbers are expected to increase.
Hepatic plants (Marchantiophyta) from the Ferreira Penna Scientific Station, Caxiuanã National Forest, Pará
Keywords: Biodiversidade; Ecossistemas amazônicos; brioflora; CNPQ::CIENCIAS BIOLOGICAS::BOTANICA